Fasciolicidal efficacy comparison between Amaro (Chuquiraga weberbaueri) and triclabendazole in calves experimentally infected with Fasciola hepatica metacercaria - Chávez, V; Vargas Rocha, L; Rojas-Moncada, J; Torrel, T (Journal of the Hellenic Veterinary Medical Society, 2025)
The Cajamarca Valley is an endemic area for Fasciola hepatica in cattle. Despite demonstrated resistance to triclabendazole, the use of this anthelmintic remains prevalent. Therefore, constant efficacy evaluations of this active ingredient are necessary, along with the exploration of alternatives for parasite control. This study aimed to determine the effectiveness of Amaro (Chuquiraga weberbaueri) and triclabendazole in controlling F. hepatica in artificially infected calves. Three groups (T0, T1, and T2) of four weaned Holstein calves each were formed and infected with 200 metacercariae. The control group (T0) received no antiparasitic treatment, group T1 was dosed with lyophilized aqueous extract of C. weberbaueri (200 mg/kg, orally, for four consecutive days), and group T2 received a single dose of triclabendazole (12 mg/kg, orally). Clinical efficacy was assessed using the Egg Count Reduction Test, and absolute efficacy was determined through necropsy. The average clinical efficacy and absolute efficacy of C. weberbaueri were 46.70% (95% CI: 33.27 – 60.13) and 58.63% (95% CI: 45.24 – 72.02), respectively. In contrast, triclabendazole demonstrated a clinical efficacy of 25.00% (95% CI: 12.62 – 37.38) and an absolute efficacy of 66.22% (95% CI: 66.22 – 79.08). Both treatments proved insufficiently active against Fasciola hepatica in calves, falling short of the category of effective fasciolicides. Nevertheless, using C. weberbaueri could be considered an environmentally friendly option to reduce the parasite burden in cattle.